1991
DOI: 10.1111/j.1699-0463.1991.tb01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactive Legionella antigens and the antibody response during infection

Abstract: Haiby, N. Cross-reactive Legionella antigens and the antibody response during infection. APMIS 99: 854-865, 1991. In order to define cross-reactive Legionella antigens suitable for diagnostic purposes, we investigated sonicate antigens from two Legionella species, including two serogroups of L. pneumophila. The antigens were reacted with heterologous and homologous rabbit antisera in Western blot. Sera from seven patients with culture-verified L . pneurnophila infection and nine patients with serologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…2A to C. Only one serum with an IgG level near the borderline range (42 U/ml) reacted with the serogroup 1 LPS, and a negative serum (26 U/ml) reacted with the serogroup 4 LPS. The blotting reagents did not contain Tween 20, because this detergent may abolish antibody binding to LPS (2), as has been demonstrated previously for meningococcal LPS (44). In our hands, no IgG binding to the serogroup 1 LPS was observed on blots with Tween 20 concentrations greater than 0.1%.…”
Section: Resultssupporting
confidence: 75%
“…2A to C. Only one serum with an IgG level near the borderline range (42 U/ml) reacted with the serogroup 1 LPS, and a negative serum (26 U/ml) reacted with the serogroup 4 LPS. The blotting reagents did not contain Tween 20, because this detergent may abolish antibody binding to LPS (2), as has been demonstrated previously for meningococcal LPS (44). In our hands, no IgG binding to the serogroup 1 LPS was observed on blots with Tween 20 concentrations greater than 0.1%.…”
Section: Resultssupporting
confidence: 75%
“…Indeed, the infectivity defects of mip mutants show that Mip is needed for optimal establishment and replication of L. pneumophila in macrophage cell lines, alveolar macrophages, blood monocytes, lung epithelial cells, amoebae, ciliates, and guinea pigs (18)(19)(20)(21)90). Other studies have shown that mip is transcribed and Mip is expressed in infected host cells (40,48,81,87), and anti-Mip antibodies are present in sera from Legionnaires' disease patients (10). The mip gene is present and expressed in other species of Legionella (9,17,41,63,66), and mip mutants of L. micdadei and L. longbeachae are also defective for intracellular infection (25,58).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated the presence of L. pneumophila serogroup-specific antigens, L. pneumophila-specific antigens, and Legionellaceae-specific antigens (14,52,53). Several investigators have attempted to identify specific antigens that could be used to improve the specificity of antibody determinations.…”
Section: Serologic Diagnosismentioning
confidence: 99%